Application of Artificial Intelligence in Various Fields - Hasanova Durdona Olim qizi (International Journal on Human-Computing Studies, 2025)
Artificial intelligence (AI) has quickly grown in importance as part of modern day digital transformation, impacting much of society. However, the integration of AI technologies across a range of sectors including education, healthcare, economics, and media has risen faster than explanatory vehicles that can inform the public about their concrete effects, their benefits, and their risks. The objective of this study is to study the function of artificial intelligence in various sectors and analyse its contribution to elements of efficiency, innovation, and human progress. This study uses qualitative analytical method grounded on worldwide literature on the ordinary uses of technology implementations and digital systems in education, healthcare, business and logistics. More specifically, systems including intelligent tutoring systems, automated data analysis tools, and diagnostic technologies for medical imaging. The functionality, efficacy, and decision making impacts of these systems are evaluated. The results also show that the AI technologies improve operational efficiency, allow the firms to provide personalised services and help in better data-driven decision making. Intelligent tutoring systems lean students towards personalized learning, while also lessening your burden as a teacher. Examples of AI driven diagnostic tools in healthcare aid in early disease identification in addition to analysis of medical images, allowing for better treatment results. Furthermore, AI not only increases economic growth by automating, digitalizing and better managing logistics. In this study, the authors argue that artificial intelligence can change a number of sectors and help us tackle tough global challenges. Nevertheless, trust in AI systems ensures its responsible governance and ethical regulation in further analysis. It must be managed, professionals developed, and ethics incorporated to play a role in sustainable human development with the help of AI.